Laser Treatment in Hirsutism: An Update - Yasmeen Jabeen Bhat; Safia Bashir; Nahida Nabi; Iffat Hassan (Mattioli1885, 2020)
Unwanted hair growth, which is a common aesthetic problem, has traditionally been treated using various techniques such as shaving, waxing, and epilation, but most of these provide only a temporary solution. Laser and light-based technology for hair removal has become one of the fastest growing procedures in modern cosmetic dermatology in the last decade. Clinical experience suggests that in the ideal subject with fair skin and dark hair, laser treatment can reduce hair growth significantly. This article reviews the various laser and light-based devices used for hair removal along with the various laser and patient parameters that affect the outcome of laser treatment for hair removal. Photoepilation, when properly used, offers clear advantages when compared with older, traditional techniques.